2007
DOI: 10.1099/mic.0.2007/006163-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal analysis of Candida albicans gene expression during biofilm development

Abstract: Microarrays were used to identify changes in gene expression associated with Candida albicans biofilm development. Two biofilm substrates (denture and catheter), and two C. albicans strains for each substrate, were tested to remove model-and strain-dependent variability from the overall dataset. Three biofilm developmental phases were examined: early (6 h), intermediate (12 h), and mature (48 h). Planktonic specimens were collected at the same time points. Data analysis focused primarily on gene expression cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
132
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(154 citation statements)
references
References 62 publications
(83 reference statements)
16
132
2
2
Order By: Relevance
“…To date, only a few genes participating in dispersion have been profi led (15,32). Our study has provided new data on the expression of two important genes encoding for adhesins Als1 and Als3, completing the earlier fi ndings (11,16,19). In agreement with them the Als1 gene was signifi cantly up-regulated in the early biofi lm stage, and the Als3 gene in the mature one.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…To date, only a few genes participating in dispersion have been profi led (15,32). Our study has provided new data on the expression of two important genes encoding for adhesins Als1 and Als3, completing the earlier fi ndings (11,16,19). In agreement with them the Als1 gene was signifi cantly up-regulated in the early biofi lm stage, and the Als3 gene in the mature one.…”
Section: Discussionsupporting
confidence: 72%
“…C. albicans adhesins Als1 and Als3 play an important role and are highly expressed in in vitro (16) as well as in vivo biofi lms (17,18). While the Als1 gene is expressed in the earlier stages of biofi lm formation (19), the Als3 gene is mainly up-regulated in the mature biofi lm (11). However, this is not a rule, as the expression of either gene can be signifi cantly affected by cultivation conditions (11,20).…”
mentioning
confidence: 75%
“…Yeater et al (2007) demonstrated, by microarray analyses of biofilms, that the expression of ALS1 increases during the early stages of biofilm development (6-12 h) and declines at the later stages. This documented profile of expression could explain why we did not observe any regulation of ALS1 under any of the conditions tested, as biofilms were grown for 48 h before analyses.…”
Section: Discussionmentioning
confidence: 99%
“…33) ALS gene family, the member encoding cell-wall glycoproteins, is an important factor for the adhesion of C. albicans. 34,35) It has been reported that ALS1 gene is expressed in the earlier stage of biofilm formation, 36) and ALS3 gene is mainly up-regulated in the mature biofilm. 37) HWP1 gene could also regulate the adhesion of C. albicans to epithelial cells by Hwp1 protein.…”
Section: Discussionmentioning
confidence: 99%